2012
DOI: 10.1021/ac3033323
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Stranded DNA Containing 8-Oxo-7,8-dihydro-2′-deoxyguanosine: Implication in the Design of Selective Aptamer Sensors for 8-Oxo-7,8-dihydroguanine

Abstract: 8-Oxo-7,8-dihydroguanine (8-oxoG, or OG) as a free base has been widely considered as a biomarker for DNA oxidative damage. Currently no fluorescence sensor has been developed to directly detect 8-oxoG less than 100 nM. In this study, two triple-stranded DNAs were selected as the scaffolds to rationally design DNA aptamer sensors for 8-oxoG. The cavity was created by deleting the 8-oxodG nucleoside in a triplex containing an A·OG-C triad or a C·OG-A triad. The results showed that the fluorescence of both senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…[26] A subsequent study demonstrated specific binding of 8-oxo-guanine. [27] Ribonucleotide complexes studied by others attract ATP or GTP via Watson-Crick and Hoogsteen base-pairing, further confirming the usefulness of the binding mode. [28,29] In our earlier work, we showed that the dissociation constants of nucleotides can reach the sub-millimolar range and that the triplex-based motifs also bind an important class of second messengers (cAMP and cGMP), [25] but we did not evaluate other functional molecules.…”
Section: Introductionmentioning
confidence: 67%
“…[26] A subsequent study demonstrated specific binding of 8-oxo-guanine. [27] Ribonucleotide complexes studied by others attract ATP or GTP via Watson-Crick and Hoogsteen base-pairing, further confirming the usefulness of the binding mode. [28,29] In our earlier work, we showed that the dissociation constants of nucleotides can reach the sub-millimolar range and that the triplex-based motifs also bind an important class of second messengers (cAMP and cGMP), [25] but we did not evaluate other functional molecules.…”
Section: Introductionmentioning
confidence: 67%
“…We first asked how the designed binding pocket may be formed without involving the termini. Unlike known triplex-based motifs, [49,51,53,54] endless-type sequences contain a bridging Figure 1. Sequences of binding motifs and their affinities for purine-containing small molecules.…”
mentioning
confidence: 99%
“…Reactive oxygen species, such as superoxide radical, singlet oxygen, hydroxyl radicals, superoxide anion and peroxyl, are considered as harmful species due to their effect on oxidative DNA damage [1,2]. 8-hydroxy-2 0 -deoxyguanosine (8-OHdG, also known as 8-oxo-7, 8-dihydroguanine and 8-oxo-dGuo) (Scheme 1), one of the main products of oxidative DNA damage, can mispair with adenine, leading to G:C-T:A transverse mutation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent sensor is the another method for 8-OHdG detection which developed in recent years. Zhang et al [2] reported a DNA aptamer fluorescent sensor for 8-OHdG determination using two triple-stranded DNAs as the scaffolds, which shows inherently insufficient binding constants between aptamers and 8-OHdG due to the small molecule of 8-OHdG.…”
Section: Introductionmentioning
confidence: 99%